Single-loop sigma delta modulator design and verification for cognitive IoT applications. Issue 3 (27th July 2020) - S., Vamsee Krishna; Reddy P., Sudhakara; Reddy S., Chandra Mohan
Abstract : Purpose: A third-order discrete time sigma delta modulator (SDM) is proposed with optimum performance by addressing instability and power dissipations issues, and a novel SDM architecture is designed and verified in behavioural modelling in MATLAB/SIMULINK environment. Simulation results show that performance parameters of proposed modulator achieved SNR of 105.41 dB, SNDR of 101.96 dB and DR of 17 bits for the signal bandwidth of 20 kHz. Design/methodology/approach: This paper describes single-loop SDM design with optimum selection of integrator weights for physiological signal processing in IoT applications. Findings: The proposed discrete time modulator designed with 1-bit quantizer and optimum oversampling ratio proved as power efficient. Integrator scaling coefficients are generated in LabVIEW environment for pure third-order noise shaping. Originality/value: This paper contains the novelty in the work, and it is suitable for cognitive Internet of Things applications.